MATERNAL MORBIDITY WITHIN 45 DAYS AFTER DELIVERY - M. Roohi; S. Mohammad alizadeh (Iran University of Medical Sciences, 2005)
It is estimated that about 6 week, after delivery mothers would recover from many change of pregnancy. But, some difficulties will remain and effect daily avidities, child care, household responsibilities and working outdoor are examples of these hardships, mostly, both mothers and health care providers do not pay attention to them. So, health problem after delivery have been called "hidden morbidity".   Therefore, in a descriptive study the researcher assessed post partum morbidities, and the prevalence of depression and fatigue in this group, and to do so, 1330 mothers were interviewed 45 days after delivery while they referred for the immunization of their babies.   Finding showed that 89% of the sample group pointed on one or more problems within 6 weeks post partum. The problems reported by mothers included: backache (52.7%), headache (49.9%), fatigue (44.4%), constipation (26.6%), postpartum blue (24.1%), breast problem (14.4%), sleep disorder (13.6%), abnormal vaginal discharge (11.1%), hemorrhoids (10.1%), stitches infection (9.6%), urinary tract infection (9.0%), side effect of anesthesia (7.4%), abnormal vaginal bleeding (5.5%), sexual problems (5.4%), urinary incontinence (2.1%), difficulty voiding (2.8%) and other problems (3.4%).   So, with such a large variety of postpartum health problems quality and quantity of care is to be considered. At antenatal care, mother and her family should be educated about post partum health problems, and health care providers should assess mothers thoroughly.